Towards harmonization of test methods for in vitro hepatic clearance studies. (March 2020) - Louisse, Jochem; Alewijn, Martin; Peijnenburg, Ad A.C.M.; Cnubben, Nicole H.P.; Heringa, Minne B.; Coecke, Sandra; Punt, Ans
Abstract: Non-animal methods for toxicokinetics, such as in vitro hepatic metabolic clearance studies, play an important role in chemical risk evaluations. To gain regulatory acceptance of such clearance data, the development of a test guideline for performing in vitro hepatic clearance studies is crucial. The aim of the present study was to obtain insight in the experimental conditions of clearance studies that influence obtained intrinsic clearance (CLint) values. To that end, in vitro hepatic CLint data obtained with rat or human hepatocytes and methodological aspects of the experiments, were collected from 42 different suitable studies published between 1995 and 2018. The CLint values for the majority of chemicals differed by more than one order of magnitude. We estimated the systematic effect of different experimental setups on the CLint values using a random forest regression analysis, revealing that 'hepatocyte concentration', 'species' (rat or human hepatocytes) and 'culture medium' have the largest impact. Calculating unbound CLint (CLint, u) values slightly reduced the variation for most chemicals. Given that in vivo clearance is in general underpredicted based on in vitro clearance data, a harmonized protocol is preferably based on a protocol that provides relatively high in vitro CLint values. Highlights: In vitro intrinsic hepatic CLint data and related information on methods used were collected from literature. Reported methods for clearance studies with rat or human hepatocytes differ for various methodological aspects. CLint values for most chemicals differ more than an order of magnitude. A random forest regression analysis point to a large effect of cell concentration and culture medium on CLint values. Harmonization of methodological aspects is required to avoid untargeted influences.